Endoscopic clipping prior to GVO vs. GVO in IGV1 bleeding: a multicenter retrospective clinical trial - Huixian Li; Dong Ye; Ping Li; Derun Kong (Endoscopy International Open, 2019)
Background and study aims Bleeding from isolated gastric varices type I (IGV1) is more dangerous and fatal than other types of esophageal variceal hemorrhages. However, optimum treatment for bleeding from IGV1 remains undefined. This retrospective study compared the efficacy of endoscopic clipping prior to N-butyl-2-cyanoacrylate injection (GVO) and only GVO for treatment of IGV1. Patients and methods Data were collected retrospectively at three medical centers. Ninety-six patients were enrolled between March 2015 and April 2017 and divided into two groups: group I (patients with endoscopic clipping prior to GVO, n = 46) and group II (patients with only GVO, n = 50). Computed tomography angiography (CTA) was performed to evaluate the status of gastrorenal shunts (GRS). Results GRS was found in 59 of 66 patients (59/66). The groups did not differ in baseline characteristics. Initial hemostasis was successfully achieved in all patients. There was a significant difference in volume of N-butyl-2-cyanoacrylate administered (3.39 ± 1.20 mL in group I versus 2.53 ± 1.05 mL in group II (P = 0.03). Rebleeding occurred in 4.35% of patients in group I and 18.00 % in group II (P = 0.007). Variceal obliteration was achieved in all patients in group I and 72 % in group II (P < 0.001) with only one session. Rate of complications was similar in both the groups with the exception of one patient in group II who developed ectopic cerebral embolism. Conclusions Endoscopic clipping prior to GVO may be an appropriate alternative to GVO as a treatment modality for IGV1 bleeding.